Personnel Management / Sixth Edition - Flippo B. Edwin (Mcgraw Hill Book Company, 1984)
Preface, Introduction, The Nature and Challenge of Personnel Management, From Mechanics to Social Responsibility, Managing the Personnel Unit, Procurement, Fair Employment Practices, Organizational and Job Design, Human Resources Planning, Recruitment and Hiring, Psychological Tests and Identification of Management Talent, Development, Individual and Organization Development, Performance Appraisal and Management by Objectives, Career Development, Compensation, Base Compensation - Job, Variable Compensation - Individual and Group, Supplementary Compensation - Fringe Benefits, Integration, Nature of Human Resource, Motivation, Quality of Work Life and Quality Circles, The Status of the Labor Union, Collective Bargaining, The Management of Conflict, Maintenance, Communication and Counselling, Safety and Health, Separation, Separation Processes, Personnel Research and Change and the Future, Indexes, Name and Subject Index.
Preface, Introduction, The Nature and Challenge of Personnel Management, From Mechanics to Social Responsibility, Managing the Personnel Unit, Procurement, Fair Employment Practices, Organizational and Job Design, Human Resources Planning, Recruitment and Hiring, Psychological Tests and Identification of Management Talent, Development, Individual and Organization Development, Performance Appraisal and Management by Objectives, Career Development, Compensation, Base Compensation - Job, Variable Compensation - Individual and Group, Supplementary Compensation - Fringe Benefits, Integration, Nature of Human Resource, Motivation, Quality of Work Life and Quality Circles, The Status of the Labor Union, Collective Bargaining, The Management of Conflict, Maintenance, Communication and Counselling, Safety and Health, Separation, Separation Processes, Personnel Research and Change and the Future, Indexes, Name and Subject Index.